Antiseizure medications: advancements, challenges, and prospects in drug development - Ng, Yan Hong; Jamil, Siti Nur Hidayah; Sarian, Murni Nazira; Ahmed, Qamar Uddin; Latip, Jalifah; Lam, Su Datt; Feroz, Shevin Rizal (Bentham Science, 2025)
Epilepsy is a neurological disorder affecting millions of people worldwide. Antiseizure medications (ASM) remain a critical therapeutic intervention for treating epilepsy, notwithstanding the rapid development of other therapies. There have been substantial advances in epilepsy medications over the past three decades, with over 20 ASMs now available commercially. Here we describe the conventional and unique mechanisms of action of ASMs, focusing on everolimus, cannabidiol, cenobamate, fenfluramine, and ganaxolone, the five most recently marketed ASMs. Major obstacles in the development of ASMs are also addressed, particularly drug-resistant epilepsy as well as psychiatric and behavioral adverse effects of ASMs. Moreover, we delve into the mechanisms and comparative efficacy of ASM polytherapy, with remarks on the benefits and challenges in their application in clinical practice. In addition, the characteristics of the ideal ASM are outlined in this review. The review also discusses the development of new potential ASMs, including modifying existing ASMs to improve efficacy and tolerability. Furthermore, we expound on the modulation of γ-aminobutyric acid type A receptor (GABAAR) as a strategy for the treatment of epilepsy and the identification of a GABAAR agonist, isoguvacine, as a potential ASM